The Impact of Smartphone Use on Children’s Mental Health: A Digital Approach Based on AI and Big Data - Damaris HOTIMA; Darius TURCIAN (Applied Medical Informatics)
This article analyzes the impact of technology on the mental health of children and adolescents, drawing from Jonathan Haidt’s research in his book The Anxious Generation [1]. The study examines the relationship between excessive use of social media, digital devices, and the increase in cases of anxiety, depression, and self-harm. By utilizing Big Data and Artificial Intelligence (AI), innovative solutions are proposed for the early detection of mental health disorders and monitoring online behavior. Additionally, personalized interventions for emotional health support, including AI-based support applications, are evaluated. Furthermore, the article explores prevention strategies such as limiting screen time, encouraging direct communication, and promoting digital education. The findings emphasize the importance of adopting effective policies for integrating technology into children's mental health management, thereby preventing the negative effects of excessive digitalization.